Bibliometric Study on the Influence of Technology on Library Transformation in Various Countries - Quddus, Zayyin Abdul (Brawijaya University Library, 2025)
Background:The digital transformation of libraries is growing rapidly with a 215% increase in scholarly publications in the last decade. Global investment in library technology reached USD 5.7 billion (2023) and is projected to increase to USD 8.4 billion (2028). However, the digital divide between countries has a significant impact on library transformation, showing significant differences in the ratio of technology adoption between developed and developing countries. Objective:This study aims to develop a comprehensive global knowledge map of technology-based library transformation through bibliometric analysis, identifying publication trends, influential authors, and key topics in digital library research. Methodology:The study used bibliometric analysis of 1,319 documents from the Scopus database published between 2015-2025 from 755 sources with 3,998 authors. Data were extracted using Bibliometrix software in R, including author information, affiliation, year of publication, keywords, and citations. Analysis was performed with the Bibliometrix and Biblioshiny packages, including visualization of collaboration networks and keyword co-occurrence. The validity of the method was confirmed through comparison with similar bibliometric studies. Results:China, the United States, and India are the dominant contributors to scientific publications with Wuhan University as the most productive institution (27 articles). There was a significant increase in publications around 2019-2021, correlating with the COVID-19 pandemic.